2019
DOI: 10.1186/s13287-019-1383-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow concentrate-induced mesenchymal stem cell conditioned medium facilitates wound healing and prevents hypertrophic scar formation in a rabbit ear model

Abstract: Background Hypertrophic scars (HSs) are formed via an aberrant response to the wound healing process. HSs can be cosmetic or can result in functional problems. Prolonged proliferation and remodeling phases disrupt wound healing, leading to excessive collagen production and HS formation. However, there are currently no satisfactory drugs to prevent HS formation. Mesenchymal stem cell (MSC) conditioned medium (CM) has therapeutic effects on wound healing and preventing HS formation. Bone marrow conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…Previous study found that caffeic acid produced low cytotoxicity of keratinocytes that can induce cell proliferation and differentiation [22]. Furthermore, another study confirmed that cell proliferation could also be elevated by means of CM from culture MSC [13]. In this study, we found treatment with MSC-CM exhibited the highest cell proliferation in both HFMSC and HaCaT keratinocyte during wound healing.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous study found that caffeic acid produced low cytotoxicity of keratinocytes that can induce cell proliferation and differentiation [22]. Furthermore, another study confirmed that cell proliferation could also be elevated by means of CM from culture MSC [13]. In this study, we found treatment with MSC-CM exhibited the highest cell proliferation in both HFMSC and HaCaT keratinocyte during wound healing.…”
Section: Discussionsupporting
confidence: 70%
“…The cytokines and growth factors play a crucial role in activating and stimulating fibroblast proliferation during the wound healing process [11]. Previous studies have reported positive results of wound healing and skin repair by utilizing CM from cultured MSCs (MSC-CM) derived from different sources such as bone marrow mesenchymal stem cell (BM-MSC) [9,12,13], adipose stem cell [14][15][16], Wharton's jelly-derived MSC [17], and human umbilical MSC [1]. Furthermore, numerous studies have proven that several kinds of drugs can be potentially used to promote cell growth and proliferation that is beneficial for wound healing and hair regeneration including UK5099 [18], sodium L-lactate (SLL) [19], lactate dehydrogenase-A (LDHA) [18], caffeine [20,21], and caffeic acid (CFA) [22].…”
Section: Introductionmentioning
confidence: 99%
“…Six studies used bone marrow MSCs: two of murine origin (Hu et al 2019(Hu et al , 2020, two of human origin , one of rabbit origin , and one study included both human and rabbit origin MSCs . Five of the studies that employed bone marrow MSCs harvested cells by needle aspiration from either the tibia, femur or posterior iliac crest (Hu et al 2019(Hu et al , 2020. One study, by Yates et al used bone marrow MSCs derived from an immortalised cell line.…”
Section: Msc Isolation and Characterisationmentioning
confidence: 99%
“…With ascending evidence in the eld of the validity of stem cell supernatant in remission of scarring [28,29], there is a good rationale for pursuing the development of ADSCC-CM as new potential therapeutic agents. Notably, α-SMA and collagen deposition related to the activity of the TGF-β/Smad2 signalling pathway participates in the transition of broblasts/myo broblasts [30].…”
Section: Discussionmentioning
confidence: 99%